He will be my ruin : a novel - Tucker, K. A. (Kathleen A.), 1978- (Atria Books, 2016)
"The USA TODAY bestselling author of the Ten Tiny Breaths and Burying Water series makes her suspense debut with this sexy, heartpounding story of a young woman determined to find justice after her best friend's death, a story pulsing with the "intense, hot, emotional" (Colleen Hoover) writing that exhilarates her legions of fans. Twenty-eight-year-old Maggie Sparkes arrives in New York City to pack up what's left of her best friend's belongings after a suicide that has left everyone stunned. The police have deemed the evidence conclusive: Celine got into bed, downed a bottle of Xanax and a handle of vodka, and never woke up. But when Maggie discovers secrets in the childhood lock box hidden in Celine's apartment, she begins asking questions. Questions about the man Celine fell in love with. The man she never told anyone about, not even Maggie. The man who Celine herself claimed would be her ruin. On the hunt for answers that will force the police to reopen the case, Maggie uncovers more than she bargained for about Celine's private life--and inadvertently puts herself on the radar of a killer who will stop at nothing to keep his crimes undiscovered"--